Odpowiedzi

2010-03-23T20:16:50+01:00
A)4x-3=3x+5
4x-3x=5+3
x=8




b)5x+2=7-3x
5x+3x=7-2
8x=6/8
x=0,75



c)3(x-1)=0
3x-3=0
3x=3/3
x=1





d) -6(x+1)=24
-6x-6=24
-6x=30/-6
x=-5



e) -7(x-2)=3x-1
-7x+17=3x-1
-10x=-18/-10
x=1,8


f)4(x-1)=6(1+x)
4x-4=6+6x
2x=10/2
x=5


a drugiego nie wiem;/
1 5 1
2010-03-23T20:19:32+01:00
Zad1. d) -6(x+1)=24
-6x-6=24
a)4x-3=3x+5 -6x=24+6
4x-3x=5+3 -6x=30 /:(-6)
x=8 x= -5
b)5x+2=7-3x e) -7(x-2)=3x-1
5x+3x=7-2 -7x+14=3x-1
8x=5 /:8 -7x-3x=-1-14
x=5/8 -10x=-15 /:(-10)
c)3(x-1)=0 x=15/10
3x-3=0 f) 4(x-1)=6(1+x)
3x=0+3 4x-4=6+6x
3x=3 /:3 4x-6x=6+4
x=3/3 -2x=10 /:(-2)
x=1 x=-5
1 1 1
Najlepsza Odpowiedź!
2010-03-23T20:20:38+01:00
A)4x-3=3x+5
4x-3x=5+3
x=8

b)5x+2=7-3x
5x+3x=7-2
8x=5|:8
x=8/5

c)3(x-1)=0
3x-3=0
3x=3|:3
x=1

d) -6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30|:-6
x=-5


e) -7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15|:-10
x=15/10
x=3/2

f)4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10|-2
x=-5
1 5 1